Astroblastoma: Radiologic-Pathologic Correlation and Distinction from Ependymoma - Port, John D.; Brat, Daniel J.; Burger, Peter C.; Pomper, Martin G. (American Journal of Neuroradiology, 2002)
Summary: Astroblastoma is a rare primary glial tumor with a characteristic appearance on neuroradiologic images. Typically, astroblastomas are large, lobulated, peripheral, supratentorial, solid, and cystic masses with relatively little associated vasogenic edema and tumor infiltration for their large size. The solid component of the mass has a bubbly appearance and a T2 signal that is isointense to gray matter. Punctate calcifications are often present. Neuroradiologists should be familiar with the characteristic appearance of this tumor.